Poriwanga Ritual Merawat Sumber Air di Desa Rombo Kecamatan Kulisusu Kabupaten Buton - Rosita Jahidin; Nasrudin Suyuti (JURNAL KABANTI: Kerabat Antropologi, 2023)
The research aims to find out the process of poriwanga ritual in Rombo Village, Kulisusu Sub-district, North Buton Regency and what meaning is contained in the poriwanga ritual in Rombo Village, Kulisusu Sub-district, North Buton Regency. The method used in this research is qualitative description with data collection techniques that combine participation observation and indepth interview techniques. The results of this study show that the poriwangaa ritual is a ritual performed to commemorate the first water source in Rombo Village. The preparation stage of the poriwanga ritual consists of three stages, namely: a) the implementation stage is the planning of the poriwanga ritual, b) the implementation stage is the main event of the traditional series of poriwanga rituals, c) the closing stage is the final activity of the series of poriwanga rituals marked by reading prayers and equalizing together around the age. The meaning contained in the poriwanga ritual is the meaning of chicken, the meaning of lapa-lapa, and the meaning of rice.